2015
DOI: 10.1142/s2010135x15300029
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free piezoelectric materials and ultrasonic transducers for medical imaging

Abstract: Piezoelectric materials have been vastly used in ultrasonic transducers for medical imaging. In this paper, firstly, the most promising lead-free compositions with perovskite structure for medical imaging applications have been reviewed. The electromechanical properties of various lead-free ceramics, composites, and single crystals based on barium titanate, bismuth sodium titanate, potassium sodium niobate, and lithium niobate are presented. Then, fundamental principles and design considerations of ultrasonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…1 Considerable progress has been made in the development of these materials, which under certain conditions display even better properties than lead containing materials. [2][3][4][5][6][7] Moreover, recent works demonstrated that ionic conductivity in NBT-based materials can be enhanced by several orders of magnitude by controlling their B-site defect chemistry. Despite the promising advancements, there is still a significant lack of knowledge considering the defect chemistry of NBT and its implications on microstructure, transport properties, and electromechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 Considerable progress has been made in the development of these materials, which under certain conditions display even better properties than lead containing materials. [2][3][4][5][6][7] Moreover, recent works demonstrated that ionic conductivity in NBT-based materials can be enhanced by several orders of magnitude by controlling their B-site defect chemistry. Despite the promising advancements, there is still a significant lack of knowledge considering the defect chemistry of NBT and its implications on microstructure, transport properties, and electromechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a large acoustic impedance mismatch existing between piezoceramics (25–35 MRayls) and body tissue (1.5 MrRayls), affects significantly the ultrasound device performance. For this reason, a matching layers elements together with its microstructure and geometry properties, being crucial for developing high performing ultrasonic transducers for medical imaging application …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, a matching layers elements together with its microstructure and geometry properties, being crucial for developing high performing ultrasonic transducers for medical imaging application. [7] The most-commonly piezoceramics materials used, the highly dense PZT ceramics with general formula Pb-(Zr x Ti 1Àx )O 3 , are characterized by high values of density and relative permittivity, which negatively influence the performance and limit their application in the ultrasonic devices. Dense PZT-type materials, in fact, show low hydrostatic figure of merit (HFOM) and poor acoustic coupling to the media with which it is in contact and are therefore not suitable for these applications.…”
Section: Introductionmentioning
confidence: 99%
“…The piezoelectric charge coefficient is the ability of the material to transfer electrical energy into mechanical waves and vice versa. We used the pulse‐echo response to check the performance of the selected sample acting an ultrasonic transducer. The measurement was carried out on a V2 standard reference block with thickness 12.5 mm, and due to the mechanical damping of the sample, a damped oscillation is produced.…”
Section: Resultsmentioning
confidence: 99%